2003
DOI: 10.1124/jpet.103.048769
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Peroxisome Proliferator-Activated Receptor γ Does Not Explain the Antiproliferative Activity of the Nonsteroidal Anti-Inflammatory Drug Indomethacin on Human Colorectal Cancer Cells

Abstract: The mechanism of the anticolorectal cancer activity of the nonsteroidal anti-inflammatory drug indomethacin is poorly understood. Indomethacin inhibits both cyclooxygenase (COX) isoforms, but it may also act via COX-independent targets. Indomethacin can bind and activate the transcription factor peroxisome proliferator-activated receptor (PPAR) ␥. Moreover, natural and synthetic PPAR␥ ligands can induce growth arrest and apoptosis of human colorectal cancer cells in vitro. Therefore, we tested the hypothesis t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…This construct had been confirmed to efficiently block the function of PPARg in HCT116 cells (24). As shown in Fig.…”
Section: Resultsmentioning
confidence: 94%
“…This construct had been confirmed to efficiently block the function of PPARg in HCT116 cells (24). As shown in Fig.…”
Section: Resultsmentioning
confidence: 94%
“…6 However, there are contradictory reports on which EP receptor(s) that mediate effects by PGE 2 , where some reports claim that main effects are mediated mainly through nuclear receptors, (PPARs), although some evidence suggests that PPAR activation does not explain antiproliferative effects by NSAIDs. [33][34][35] Genetic deletion/inhibition of EP receptors and the use of antagonists/agonists have concluded that EP 1 and EP 4 , but not EP 2 and EP 3 , reduced colon adenoma formation in mice. 26,27 On the other hand, studies of mRNA expression in rat colon carcinogenesis showed overexpression of EP 1 and EP 2 , but not of EP 3 and EP 4 when compared to normal colon mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, a number of NSAIDs, including indometacin, have been shown to behave as PPAR γ ligands 64 . The antineoplastic effects of the NSAID indometacin in vitro , however, do not seem to be mediated through PPAR γ 65, 66 . Thirdly, the COX‐2 promoter contains a peroxisome proliferator response element that can bind PPAR γ ligands 67 .…”
Section: Pparγ Ligandsmentioning
confidence: 99%